PERAWATAN LUKA DIABETIK DI RUMAH PADA PASIEN DIABETES MELLITUS YANG PERNAH DIRAWAT DI RUMAH SAKIT - Nurul Hidayah; Rahmi Syarifatun Abidah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2024)
Diabetic ulcers is a malfunction of continuity tissue in patients diabetes mellitus uncontrolled and undergoes necrosis tissue a consequence of the disorder blood vessels, neuroscience disorder, and infection. The treatment of injuries retinopathy at home is a aseptic clean and washing a sore and ended choose swathe proper . Diabetic ulcers makes the impact and problems in the family, especially in a process the treatment of injuries done by the family. Phenomena found dressing a wound that “less” in people with gangrene in RSUD Bangil Kabupaten Pasuruan. The treatment of injuries bad in diabetes will result in a serious health problem of them amputation feet. The purpose of this research has described the treatment of injuries retinopathy when the home was done by the to diabetics Mellitus.The kind of research used is research descriptive. This research using technique sampling consecutive sampling with the number of respondents 30 people .Technique data collection use sheets of observation .The result of research preparation in treating wound 47 % good , treatments in cleansing a wound 43 % less , wound dressing 40 % enough .The treatment of injuries retinopathy when home in people with diabetes mellitus that ever were treated at the Bangil hospital Kabupaten Pasuruan 40 % good .Good enough lack of the treatment of injuries retinopathy home depends on the way the treatment , of a common purpose, is known 40 % category good .It was because preparation in treating a wound that good and wound dressing enough although treatments in cleansing a wound is weak .For health institutions to give the treatment of injuries retinopathy good and education health or information about the treatment of injuries home good , so that degrees healing can be increased .